2009
DOI: 10.15288/jsads.2009.s16.34
|View full text |Cite
|
Sign up to set email alerts
|

Screening for High-Risk Drinking in a College Student Health Center: Characterizing Students Based on Quantity, Frequency, and Harms

Abstract: ABSTRACT. Objective: This study examined characteristics of students who presented to a college health center and screened positive for the 5/4 defi nition of high-risk drinking (fi ve or more drinks in a row for men, or four or more drinks in a row for women, on at least one occasion in the past 2 weeks) and analyzed the students' data according to their reporting of alcohol-related harms. Method: Secondary analysis of data obtained for an intervention study to reduce high-risk drinking in college students wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
1
19
0
2
Order By: Relevance
“…Proactive guidelines recommend screening and physician advice, which could help address this common cause of injury and premature death. [2][3][4][5][6][7] Recent reviews of clinical trials found alcohol brief interventions to be effective in adults in the United States, 8,9 among college students, [10][11][12][13] and cross-nationally. 14 In the United States, unhealthy alcohol use is the third leading preventable cause of death, 15 causing over 71,000 deaths annually and shortening the lives of those who die by approximately 30 years on average.…”
Section: Introductionmentioning
confidence: 99%
“…Proactive guidelines recommend screening and physician advice, which could help address this common cause of injury and premature death. [2][3][4][5][6][7] Recent reviews of clinical trials found alcohol brief interventions to be effective in adults in the United States, 8,9 among college students, [10][11][12][13] and cross-nationally. 14 In the United States, unhealthy alcohol use is the third leading preventable cause of death, 15 causing over 71,000 deaths annually and shortening the lives of those who die by approximately 30 years on average.…”
Section: Introductionmentioning
confidence: 99%
“…Among adults, strong compelling evidence supports the need for and effectiveness of screening and brief intervention for unhealthy alcohol use. [1][2][3][4][5][6][7][8] Unhealthy use is a spectrum of consumption, including binge drinking, abuse, and dependence, which poses health risks. 5 Proactive guidelines recommend screening and physician advice to reduce this common cause of injury and premature death.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Unhealthy use is a spectrum of consumption, including binge drinking, abuse, and dependence, which poses health risks. 5 Proactive guidelines recommend screening and physician advice to reduce this common cause of injury and premature death. [8][9][10][11][12][13] In 2004 and 2012, the US Preventive Task Force recommended screening and behavioral counseling interventions to reduce unhealthy alcohol use by adults, 14,15 but indicated that evidence regarding these practices for adolescents was insufficient.…”
Section: Resultsmentioning
confidence: 99%
“…Fourth, Schaus et al (2009a) examined the characteristics of students who presented to a university health center and screened positive as high-risk drinkers according to the 5/4 defi nition of heavy episodic drinking-that is, for men, fi ve or more drinks in a row on one or more occasions in the past 2 weeks and, for women, four or more drinks in a row. Nonheavy drinkers, heavy drinkers, and frequent heavy drinkers (who drank heavily three or more times in the past 2 weeks) had mean scores of 10, 14, and 23, respectively, on the Rutgers Alcohol Problem Index.…”
Section: Studies To Inform Future Intervention Researchmentioning
confidence: 99%